+0  
 
0
295
2
avatar

(2^2)^-2

Guest Apr 11, 2017
 #1
avatar
0

it = 0.0625

Guest Apr 11, 2017
 #2
avatar+92751 
+3

(2^2)^-2

 

\((2^2)^{-2}\\ =4^{-2}\\ =\frac{\color{blue}{1} *\color{black}4^{-2}}{1}\\ =\frac{\color{blue}{1} }{1*\color{black}4^{+2}}\\ =\frac{\color{blue}{1} }{\color{black}4^{2}}\\ =\frac{\color{blue}1 }{\color{black}16}\\ \)

Melody  Apr 11, 2017

13 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.